The diasporic cinema of Mira Nair - Varga, Zsanett (AMERICANA E-journal of American Studies in Hungary, 2018)
The article analyses the ways in which Nair first focuses on the notions of authenticity, tradition and nostalgia that shift from her initial films into Nair’s feature length films. Nostalgia together with the aspect of the displaced home is pivotal for the director’s diasporic cinema. The article focuses on The Namesake (2006) and The Reluctant Fundamentalist (2012), as well as on earlier Nair movies such as the Mississippi Masala (1991) and Salaam Bombay! (1989).